The Propensity for Mandatory Audit Rotation and its Impact on Earnings Management in Europe - Reicher, Regina; Bao Ngo, Tran Nguyen (International Journal of Engineering and Management Sciences, 2020)
The doubt of investors for the accuracy of financial reporting statements and the credibility of external audit functions has becoming more and more severe in the recent years due to a variety of booming accounting scandals related to earnings management occurring around the world. To cope with these serious frauds in the world of financial market, many countries have adopted Mandatory Audit Rotation (MAR) rules. Although the MAR rule has been valid around European Union (EU) members since 2016, the effectiveness of this rule has not been examined in any academic papers yet. As a result, the aim of this study is to investigate the effectiveness and the necessity of the latest MAR rule in the EU by testing the influence of audit rotation activities and audit tenure on earnings management of companies in the STOXX Europe 600 Index. Practical implications of this study will not also prove whether companies in STOXX Europe 600 Index should be required to shorten their audit tenure by rotating their audit engagement more often in order to decline the degree of earnings management, but they will also help to strengthen support for the essentiality of MAR legislations in the EU if the result indicates that longer audit tenure actually leads to more earnings management of STOXX Europe 600 Index companies.